NILAI RELIGIUS DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR NEGERI 003 PAGARSIH - Maulana Syarif Hidayat FJ Maulana Syarif Hidayat FJ; Opik Taupik Kurahman Opik Taupik Kurahman (MGMP PAI Jawa Barat, 2023)
The purpose of this study was to determine the religious value of the independent curriculum implemented at Pagarsih 003 Public Elementary School. The research method in this paper is descriptive qualitative by collecting good data from books, journals, observations, and interviews related to this mini research. The religious values of the independent curriculum implemented in Pagarsih 003 Public Elementary School, namely: relating to faith and piety, namely carrying out every Tuesday-Friday reading short letters and Asmaul Husna together in the field, carrying out Islamic holiday commemorations, carrying out sacrifices at school, to the noble character of students is required to carry out 5 S (polite, polite, smile, greet, greeting,) every day, incalculating global diversity values for students carried out by teachers in each subject while studying in class so that they always live in harmony and have an attitude of tolerance, for the independence of students, namely students who are able to clean the class on their own without being asked by the teacher, are able to do assignments independently, do not cheat during exams, while mutual cooperation activities at school carry out fundraising for victims of natural disasters/social services, cleaning places of worship and classes together, while for creativity vitas by making works such as calligraphy, craft art or so on and there are always creative works in every subject.